Descriptive study of patients related to COVID-19 pandemic attending psychiatric clinic in Gwalior city - Changulani, Richa; Shukla, Durgesh; Mishra, Ashok; Changulani, Mukesh (International Journal Of Community Medicine And Public Health, 2020)
Background: The COVID-19 pandemic and subsequent lockdown has adversely affected the lives and livelihood of millions in our country. This has played havoc on the psychological health of a large section of our population. It is not known, however, whether this has led to an increase in the number of patients of psychiatric disorders. With this aim, this study was planned. Methods: An observational study was done on 100 participants who visited the private psychiatric outpatient clinic of Gwalior district between mid-May to mid-September. Data entry and statistical analysis was done in MS-Excel Software. Results: Out of 926 patients with no previous history of psychiatric illness who attended the clinic for the first time, 100 (10.8%) patients had illness as a direct consequence of stress of COVID 19 and subsequent lockdown. The majority were Hindu (87%), males (65%), general category (63%) and 96% were residing in urban areas. 56%, 13% and 10% of patients had Moderate depression, Panic disorder and Anxiety disorder respectively. The precipitating reason for their illnesses turned out to be: fear of viral infection (56%), uncertainty of the situation (90%), losing their source of income (61%), Frustration, boredom and lack of social contact. Conclusions: In our study, young male participants emerged as risk group. Maximum participants were facing fear of infection, fear of loss of career, uncertainty, frustration due to boredom and lack of social contact as factors of psychiatric health concern.